Building information modelling (BIM) capabilities in the design and planning of rural settlements in China: A systematic review - Cao, Yu (MDPI, 2022)
With rural revitalization being established as the national policy in China, the environmental quality and residential comfort of rural settlements has received widespread attention from the whole society in China. However, due to the over-exploitation of resources and the uneven development between urban and rural in China, the environmental conditions and residential experience in rural settlements in China are still relatively backward. To prompt the environmental quality and residential comfort of rural settlements in China, it is necessary to optimize the planning and design of rural settlements in China. As a multi-function method, Building Information Modeling (BIM) can significantly contribute to the planning and design of rural settlements in China. To optimize the environmental quality and residential experience in rural settlements in China, this study is developed to perform a systematic literature review of the BIM capabilities in the design and planning phase of rural settlements in China. To achieve this aim, the PRISMA protocol was used to perform this systematic review. The review and discussion of this study were conducted between June 2022 and September 2022. In this study, Web of Science (WoS) and Scopus were adopted as the main databases, and 189 articles were reviewed. Through this systematic review, it can be identified that BIM capabilities have significant advantages in the following aspects of the design and planning of rural settlements in China: Data storage and management; 3D modeling and visualization; Disaster prevention and environmental analysis; Cost estimation and optimization. Furthermore, through the discussion and analysis of research results, it can be concluded that BIM capabilities can perform their benefits in the rural settlements' design and planning through their following characteristics: knowledge management, simulation, and modeling. Based on the research results, it can be identified that knowledge management capabilities in BIM can effectively provide information support and knowledge assistance throughout the design and planning phase of rural settlements in China. BIM's simulation and modeling capabilities can simulate and demonstrate the rural environment and their internal structures in rural settlements' design and planning phase to achieve their environmental optimization, residential comfort improvement, clash detection, disaster prevention, and expenditure reduction. Moreover, the challenge and future directions of BIM capabilities in the design and planning phase of rural settlements in China are discussed and analyzed. This study can effectively promote and optimize the BIM utilization in the design and planning phase of rural settlements in China, to better enhance their environmental quality and residential experience.